2020
DOI: 10.1080/00221546.2020.1795504
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Selective College Admissions Criteria in Interrupting or Reproducing Racial and Economic Inequities

Abstract: Selective colleges have increasingly considered a variety of factors, such as academic rigor, extracurriculars, essays, interviews, recommendations, and background characteristics, alongside traditional academic factors in determining who is admitted. These efforts have been hailed as a strategy to expand access to selective higher education for talented students from racially and economically marginalized backgrounds. But such efforts introduce ambiguous admissions criteria-excellence in extracurriculars, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…In addition to the individual's concentration on empowerment, the variety of programs offered, sustainability and empowerment processes are also determinants of self-efficacy in increasing performance. Kudo & Mori (2015), statement regarding individuals who have high self-efficacy will show skills in training well, which is also supported by the results of this study, self-efficacy increases the influence of empowerment programs, empowerment processes and outputs on MSME performance (Anderman & Patrick, 2012;Rosinger et al, 2021).…”
Section: Resultssupporting
confidence: 76%
“…In addition to the individual's concentration on empowerment, the variety of programs offered, sustainability and empowerment processes are also determinants of self-efficacy in increasing performance. Kudo & Mori (2015), statement regarding individuals who have high self-efficacy will show skills in training well, which is also supported by the results of this study, self-efficacy increases the influence of empowerment programs, empowerment processes and outputs on MSME performance (Anderman & Patrick, 2012;Rosinger et al, 2021).…”
Section: Resultssupporting
confidence: 76%
“…Essays are intended to provide information about an applicant's resources, conditions for learning, and personal characteristics such as motivation, resilience, leadership, and self-confidence. The expressed purpose of admission essays, and of holistic review more generally, is to enable consideration of applicant attributes beyond what is captured in a few easily comparable numbers (12,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…With dramatic reductions in test scores submitted-due to either constrained testing availability or shifting student preferences-admissions decisions place increased reliance on extracurriculars and subjective factors such as letters of recommendation. Prior research has found increased weight on such elements to be adversely related to Pell Grant recipient enrollment (Rosinger et al, 2021). Accordingly, there remains value in considering the equity implications of the admission criteria still in place at test-optional institutions and potentially expanding those criteria to include additional factors (e.g., Melguizo, 2010).…”
Section: Discussionmentioning
confidence: 99%